121 The Cumulative Effect of Evidence-Based Practices on Outcomes of Preterm Infants Born <29 Weeks - Rizzolo, Angelo (Paediatr Child Health, 2019)
BACKGROUND: Extremely preterm infants born <29 weeks’ gestation are at high risk of death or severe neurological injury (SNI; ≥grade 3 intraventricular hemorrhage and/or periventricular leukomalacia). Individual studies of four evidence-based practices (EBPs) have been associated with reductions in death/SNI. OBJECTIVES: To investigate the cumulative effect of four EBPs and their association with death/SNI among infants born <29 weeks. DESIGN/METHODS: Observational study of infants born 23(0)-28(6)weeks admitted in NICUs participating in the Canadian Neonatal Network from 2013–2017.EBPs included: antenatal MgSO(4)for neuroprotection (MgSO(4)), antenatal corticosteroids (ACS), delayed cord clamping ≥30 seconds (DCC)and normothermia on admission (NT). The effect of exposure to one, two, three and all four EBPs was assessed using multivariate logistic regression models adjusted for patient characteristics. RESULTS: Rate of death/SNI was 26% (966/3788) in the cohort. Rate of exposure to EBPs was: none, 3% (132); one, 16% (606); two, 36% (1362); three, 33% (1267); all, 11% (421). Significantly lower odds of death/SNI were observed with exposure to ACS (adjusted odds ratio [AOR] 0.60, 95% CI 0.50–0.72) and DCC (AOR 0.77, 95% CI 0.61–0.98) but not with MgSO4(AOR 0.87, 95% CI 0.71–1.05) and NT (AOR 0.93, 95% CI 0.55–1.13). Infants exposed to two EBPs had significantly lower odds of death/SNI than those not exposed to any EBPs (25% [346/1362] vs 37% [49/132], AOR 0.70, 95% CI 0.66-0.60). Exposure to increasing number of EBPs was associated with decreasing odds of death/SNI (Table 1). CONCLUSION: Among infants born <29 weeks’ gestation, exposure to higher number of EBPs is associated with decreasing odds of death/SNI. Increasing compliance with implementation of these four EBP should be the goal to improve outcomes. [Image: see text]